1999
DOI: 10.1086/514731
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia in Cancer Patients: A Prospective, Multicenter Surveillance Study by the Invasive Fungal Infection Group (IFIG) of the European Organization for Research and Treatment of Cancer (EORTC)

Abstract: In a surveillance study of candidemia in cancer patients that was conducted by the European Organization for Research and Treatment of Cancer, 249 episodes were noted; Candida albicans was isolated in 70% (63) of the 90 cases involving patients with solid tumors (tumor patients) and in 36% (58) of the 159 involving those with hematologic disease (hematology patients). Neutropenia in tumor patients and acute leukemia and antifungal prophylaxis in hematology patients were significantly associated with non-albica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
345
2
16

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 544 publications
(395 citation statements)
references
References 28 publications
32
345
2
16
Order By: Relevance
“…9,32 Other studies including the SCOPE project have identified C. parapsilosis in 4% to 11% of patients with fungemia. 2,4 By contrast, C. parapsilosis was the etiologic agent of candidemia in 29% of neonatal ICU patients in the NEMIS study. 9 Historically, C. parapsilosis has accounted for 3% to 27% of cases of fungemia in large hospital-based studies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…9,32 Other studies including the SCOPE project have identified C. parapsilosis in 4% to 11% of patients with fungemia. 2,4 By contrast, C. parapsilosis was the etiologic agent of candidemia in 29% of neonatal ICU patients in the NEMIS study. 9 Historically, C. parapsilosis has accounted for 3% to 27% of cases of fungemia in large hospital-based studies.…”
Section: Discussionmentioning
confidence: 92%
“…2 C. albicans has historically been the most frequently isolated species, accounting for approximately 60% to 70% of the infections; however, recent studies have documented an increase in the proportion of infections due to non-albicans species. [1][2][3][4][5][6][7][8][9][10][11] Previous studies have suggested several risk factors for the acquisition of a nosocomial candidal bloodstream infection. 2 These data are somewhat limited by the fact that many of the epidemiologic studies focused on specific patient populations, were observational in nature, and were conducted prior to the era of increased use of azoles.…”
mentioning
confidence: 99%
“…All patients with persistent fungemia were evaluated for secondary ocular, endovascular, and joint infections. Neutropenia was defined as absolute neutrophil count (ANC) Ͻ500 cells/mm 3 and ANC of Ͻ100 cells/mm 3 was regarded as profound granulocytopenia. Agranulocytosis was a non-detectable neutrophil count in peripheral circulation.…”
Section: Definitionsmentioning
confidence: 99%
“…[1][2][3][4] In recipients of blood and marrow transplantation, systemic candidiasis is a serious complication associated with high morbidity and mortality. 5,6 Antifungal prophylaxis with fluconazole during the early post-transplantation period has been shown to significantly reduce the incidence of candidemia, 7 and improve short-term survival.…”
mentioning
confidence: 99%
“…2 A prospective multicenter surveillance study showed a mortality rate of about 40% within 30 days after the onset of candidemia in patients with leukemia. 3 Major risk factors for IFI in SCT patients include long-lasting neutropenia, compromised granulocyte and macrophage functions, depression of cellular and humoral immunity as a consequence of severe GVHD and/or immunosuppression, breakdown of natural antimicrobial barriers owing to chemotherapy-related mucositis, indwelling venous catheters and/or alterations of the endogenous microflora. 1 The most common pathogens that cause deep fungal infections are Candida and Aspergillus spp., but with increasing frequencies, uncommon fungal pathogens such as Trichosporon spp., Zygomycetes and Fusarium spp.…”
Section: Introductionmentioning
confidence: 99%